2004
DOI: 10.1002/ddr.10415
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxin III induces apoptosis in T24 cells via reactive oxygen species‐independent mitochondrial death pathway

Abstract: Cardiotoxin III (CTX III), a basic polypeptide with 60 amino acid residues isolated from Naja naja atra venom, has been reported to have anticancer activity. CTX III inhibited the growth of T24 cells in a time-and dose-dependent manner with an IC 50 value of 1.7 mg/mL and displayed several features of apoptosis including apoptotic body formation, increase of sub G 1 population, DNA fragmentation, and poly (ADP-ribose) polymerase (PARP) cleavage. Using apoptosis analysis, measurement of reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These toxins show preferential cytotoxicity towards cancer cells, probably mediated by inhibition of protein kinase C activity or through a membrane fusion effect 18–20 . Previous studies have shown that CTX III exhibits cytotoxic activity against T24 (human bladder cancer), K562 and HL‐60 (human leukaemia), Colo205 (human colorectal cancer), MCF‐7 (human breast adenocarcinoma) and Ca9‐22 (oral squamous cell carcinoma) cells 21–27 . Nevertheless, the cellular signalling pathways involved in these effects of CTX III remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These toxins show preferential cytotoxicity towards cancer cells, probably mediated by inhibition of protein kinase C activity or through a membrane fusion effect 18–20 . Previous studies have shown that CTX III exhibits cytotoxic activity against T24 (human bladder cancer), K562 and HL‐60 (human leukaemia), Colo205 (human colorectal cancer), MCF‐7 (human breast adenocarcinoma) and Ca9‐22 (oral squamous cell carcinoma) cells 21–27 . Nevertheless, the cellular signalling pathways involved in these effects of CTX III remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Previous studies have shown that CTX III exhibits cytotoxic activity against T24 (human bladder cancer), K562 and HL-60 (human leukaemia), Colo205 (human colorectal cancer), MCF-7 (human breast adenocarcinoma) and Ca9-22 (oral squamous cell carcinoma) cells. [21][22][23][24][25][26][27] Nevertheless, the cellular signalling pathways involved in these effects of CTX III remain unknown. In the present study, the apoptotic effects of CTX III on A549 cells were investigated, with particular emphasis on the signalling pathways involved.…”
Section: Introductionmentioning
confidence: 99%